MONITORING OF CONDITIONS THROUGH THE HOSPITAL AVOIDANCE INDICATOR - Rodrigues, Alexsandro; Cristine da Silva, Suellen; do Monte Massela Malta, Arlete; Zanatelli, Carla; de Matia, Graciele; Teresinha Franco Rotta, Roseana; Cícero da Silva, Luciano; Moraes, Gabriela (Health and Society, 2023)
This proposal for problem of hospital evasion is based on the measurement of data through a hospital evasion indicator, which measured the data obtained with the intention of investigating the number of patients who had to leave the hospital early without the medical consent, registered in the period between September 2022 and January 2023, as this is a period with a higher incidence of cases due to the end of year festivities, were patients feel tempted to be with their family members to social gatherings, contributing to the increase in hospital avoidance. Monitoring this problem, monitors, evaluates and proposes effective methods to reduce this problem with changes in the medical-hospital routine.